Implementation of Parents Teacher Conferences for English Lessons - Fatimah Zuhra; Usman Kasim; Asnawi Muslem (Universitas Syiah Kuala, 2018)
This research focused on analyzing teacher’s implementation of parents-teacher conference assessment at SD Teuku Nyak Arif Fatih Bilingual School. The objectives of this study were to specify the implementation of recommendations from a parents-teacher conference by the English teacher in the English lessons. The method used in this research was a qualitative research design. The instruments used to collect the data were observation sheets from the parents-teacher conference made by the teacher plus an interview guide. The collected data was analyzed using descriptive qualitative analysis. The findings showed that the teacher used three steps with the parents-teacher conference: (1) before the conference (2) during the conference and (3) after the conference. The teacher adopted all the steps recommended by experts. The researcher suggests that English teachers and students use parents-teacher conferences as part of their assessment in their teaching-learning processes since the results from parent-teacher conferences are very useful for the teachers and their students.